الامتحانات عبر الإنترنت في سياقات الطوارئ: هل المراقبة، والتقنيات الأخرى، مجدية في سوريا لتيسير عقد امتحانات تشمل جميع الطلاب؟ - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; AlMekdad, Bayan; Sabboura, Rani; Sheqem, Yazeed (EdTech Hub, 2022)
كلمات مفتاحية: الامتحانات عبر الإنترنت، تكنولوجيا مراقبة الامتحانات، سياقات الطوارئ، سوريا خلاصة: الغرض من هذه الوثيقة تقديم دليل يمكن استخدامه من قبل الممارسين في مجال التعليم العاملين في سياقات الطوارئ لتقييم مدى جدوى تنفيذ الامتحانات الإلكترونية واستخدام تكنولوجيا مراقبة الامتحانات. سيتطلب عقد الامتحانات عالية المخاطر عبر الإنترنت في سوريا وفي سياقات طوارئ أخرى استثمارات كبيرة لتحقيق المتطلبات الأساسية اللازمة للجدوى والمصداقية. تشمل هذه المتطلبات الأساسية الكهرباء والإنترنت والأجهزة، بالإضافة إلى تطوير المهارات الرقمية اللازمة للطلاب لتقديم الامتحانات عبر الإنترنت وللمعلمين والإداريين لتيسير الامتحانات عبر الإنترنت. ينبغي بذل المزيد من الجهود لمنع تسريب المعلومات حول الأسئلة ومحتوى الامتحانات، ولتشجيع التغيير الثقافي حول الامتحانات عبر الإنترنت. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7143871 ZenodoArchiveConcept: 7143870 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7143871 10.53832/edtechhub.0124 2405685:9DZXFIC7
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen